GENERALIZED THOM SPECTRA AND THEIR TOPOLOGICAL HOCHSCHILD HOMOLOGY. (2nd November 2017) - Basu, Samik; Sagave, Steffen; Schlichtkrull, Christian
Abstract : We develop a theory of $R$ -module Thom spectra for a commutative symmetric ring spectrum $R$ and we analyze their multiplicative properties. As an interesting source of examples, we show that $R$ -algebra Thom spectra associated to the special unitary groups can be described in terms of quotient constructions on $R$ . We apply the general theory to obtain a description of the $R$ -based topological Hochschild homology associated to an $R$ -algebra Thom spectrum.